2016
DOI: 10.1590/1807-2577.07315
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a heating device and adhesive temperature on bond strength of a simplified ethanol-based adhesive system

Abstract: ResumoIntrodução: O aumento da temperatura do adesivo tem sido pesquisado como forma de melhorar a evaporação do solvente, reduzir a viscosidade e melhorar a permeação dos monômeros na dentina. Objetivo: Investigar a influência de diferentes métodos de aquecimento na resistência de união à dentina sob um ensaio de microtração de um adesivo de condicionamento ácido total. Material e método: Vinte e quatro terceiros molares hígidos foram seccionados transversalmente a fim de expor a superfície plana da dentina. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…In our previous study 8) , it was confirmed that the bond strength of both 1-step SEs 21) and universal systems 16) could be significantly influenced by prolonging air-blowing time appropriately. As one of the most important variables of the air-blowing application, the air temperature ranged from 37ºC to 80ºC was investigated in previous studies 10,20,[22][23][24][25][26][27] . Among these studies, the effect of evaporation temperature around 37ºC still seems controversial with the uncertain detrimental impact 20,27) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study 8) , it was confirmed that the bond strength of both 1-step SEs 21) and universal systems 16) could be significantly influenced by prolonging air-blowing time appropriately. As one of the most important variables of the air-blowing application, the air temperature ranged from 37ºC to 80ºC was investigated in previous studies 10,20,[22][23][24][25][26][27] . Among these studies, the effect of evaporation temperature around 37ºC still seems controversial with the uncertain detrimental impact 20,27) .…”
Section: Discussionmentioning
confidence: 99%
“…3G, H) within the adhesive layer. Hence, the warm air should be considered as an effective way to increase the bond strength of HEMA-free acetone-based adhesive by removing the residual moisture in the adhesive layers 10,19,[21][22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…After reading the full text, nine articles were excluded due to several reasons: in (4), the bond strength was not evaluated [18,[30][31][32]; in (4), a warm air stream was not tested [33][34][35][36]; and (1) was a thesis [37]. Then, a total of 28 articles were included in the qualitative analysis [12][13][14]16,20,21,23,24,29,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56]. One study was excluded from the meta-analysis because there were no more studies for comparison [53].…”
Section: Resultsmentioning
confidence: 99%
“…Carvalho et al 7 verificaram a influência do aquecimento e da temperatura do adesivo na resistência de união de um sistema adesivo à base de etano, sendo baseado na afirmação de que o aumento da temperatura do adesivo auxilia na liberação do solvente, reduzindo a viscosidade e auxiliando na penetração dos monômeros na dentina. Foram elaborados 3 grupos, sendo o primeiro o grupo controle, o segundo grupo foi conseguido por meio de um dispositivo de aquecimento, até a temperatura de 37 graus e o terceiro usou-se um jato de ar quente para esquentar as amostras para a preparação dos corpos de prova.…”
Section: Revisão Da Literaturaunclassified